Povement patterns of Polish national Paralympic team wheelchair fencers with regard to muscle activity and co-activation time - Borysiuk, Z.; Blaszczyszyn, M.; Piechota, K.; Nowicki, T. (Journal of Human Kinetics, 2022)
The aim of this study was to determine muscle co-activation and muscle activity time using EMG in Paralympic wheelchair fencers categorized into two disability-level groups: A (n= 7) and B (n= 9). The study was carried out with the use of a 16-channel EMG system. The surface EMG electrodes were placed on the fencer`s body along nine channels: arm muscles - deltoideus middle head (DEL), triceps brachii (TRI) and biceps brachii (BC); forearm muscles - extensor carpi radialis longus (ECR), flexor carpi radialis (FCR); postural (abdominal and back) muscles - the right and the left external oblique abdominal (EOA RT and LT) and latissimus dorsi (LD RT and LT). To assess the relative level of co-activation (simultaneous contraction of both muscles) for the TRI-BC, ECR-FCR, LD RT-EDA RT and LD LT-EDA LT muscle pairs, the co-activation index (CI) was calculated. The collected data were processed using Jamovi. The study hypotheses were verified at the level of significance of p=0.05 (Welch`s t-test). The normal distribution of analyzed statistical features was checked with the Shapiro-Wilk test. The analysis of muscle activation time, as a percent ratio of three attempts executed in a series, confirmed the study assumptions. Fencers from Group A had a shorter activation time in all tested muscles, with the exception of the ECR (58.24), than fencers from Group B. This confirms that the activation of antagonist muscles representing a centrally programmed anticipatory mechanism stabilizing technical actions was particularly intensified in Group A fencers. The study results indicate that the standard co-activation index (CI) of key muscles involved in wheelchair fencing ranges from 48 to 51%.